Modified Early Warning Score (Mews): desenvolvimento de software para preenchimento digital, implantação e avaliação do uso em setores de enfermaria clínica e cirúrgia de um hospital de ensino - Souza, Davi Tamamaru de (2024)
Patient safety is a global concern and one of the fundamental principles of healthcare, with a direct impact on the quality of care. It is estimated that between 14% and 28% of admissions to intensive care units (ICUs) result from unplanned transfers. Evidence indicates that patients often show signs of physiological instability before clinical deterioration occurs. Therefore, a tool capable of identifying these patients early on is essential. The Modified Early Warning Score (MEWS) is used to identify patients at risk of clinical deterioration. However, simply implementing MEWS to identify high-risk patients does not guarantee clinical interventions that can mitigate or prevent such deterioration. In this context, the present project aimed to develop a software for digital completion and implementation in the clinical and surgical wards of a teaching hospital. Two scientific articles were developed: the first reports the nursing staff’s experience with the implementation of MEWS in the wards, using the software as a facilitator, and the second addresses the applicability of the software by the nursing team. It was concluded that the experience of implementing MEWS was considered positive, providing greater autonomy to the nursing staff, improving interprofessional communication, and enhancing patient safety. Regarding usability, the software was rated as “best imaginable” according to the System Usability Scale. It is expected that MEWS calculated through the software can be adopted as an institutional tool in all sectors of the teaching hospital.